Hubungan kekuatan otot lengan dan koordinasi mata tangan dengan kemampuan servis atas bola voli pengembangan diri di Smk negeri 1 tembilahan - Irwan syahputra Irwan; Andriansyah; Prima Antoni (Indra Institute Research & Publication, 2026)
This study aims to determine the relationship between arm muscle strength and hand-eye coordination and the ability to perform an overhand serve in volleyball among students participating in the Personal Development program at SMK Negeri 1 Tembilahan. This study employed a quantitative method using a correlational research design. The study population consisted of 14 students, all of whom were included in the sample using a saturation sampling technique. Data collection was conducted through a push-up test to measure arm muscle strength, a ball-throwing-and-catching-against-a-wall test to measure hand-eye coordination, and a volleyball overhand serve test to measure overhand serving ability. Data analysis utilized the product-moment correlation and multiple correlation. The results showed a significant relationship between arm muscle strength and the overhand volleyball serve ability (r = 0.627; 39% contribution). Eye-hand coordination also had a significant relationship with the overhand volleyball serve ability (r = 0.963; 92% contribution). Furthermore, arm muscle strength and eye-hand coordination simultaneously showed a significant relationship with the overhand serve ability in volleyball (R = 0.965) with a contribution of 93%, which falls into the category of a very strong relationship. Based on the research findings, it can be concluded that arm muscle strength and hand-eye coordination are significantly associated with the ability to perform an overhand serve in volleyball among students participating in the Personal Development program at SMK Negeri 1 Tembilahan.